Effect of Replacement of Barley Grains by Wasted Bread Crumbs or Rejected Dates on Growth Performance and Carcass Traits of Growing Rabbits - AL-Shami, S.A.; Mohammed, T.A. (Pakistan Journal of Nutrition, 2009)
Thirty five 10 weeks of age white New Zealand rabbits were assigned to investigate the effect of partial and complete replacement of barley grains by Wasted Bread Crumbs (WBC) or Rejected Dates (RD) on growth performance and carcass traits of growing rabbits. The rabbits were allotted into seven groups (5 rabbits per each). Seven diets were formulated, the control (No. 1) based on barley grains as the main energy source and the tested alternative energy sources (WBC and RD) replaced 33.33, 66.66 and 100% from the barley quantity of the control to formulate 6 diets respectively. The diets were offered for 40 days. The results indicated that WBC inclusion (15 or 30%) reduced (p>0.05) body weight, Daily Body Gain (DBG), Daily Feed Intake (DFI) and deteriorated Feed Conversion (FCR), Protein Efficiency Ratio (PER) and Efficiency of Energy Utilization (EEU) when compared with control, however, the higher inclusion level of WBC reduced (p